Precise measurement of the top-quark mass from lepton jets events - Abazov, V. M.; Abbott, B.; Abolins, M.; Acharya, B. S.; Adams, M.; Adams, T.; Aguilo, E.; Ahsan, M.; Alexeev, G. D.; Alkhazov, G.; Alton, A.; Alverson, G.; et al. (American Physical Society (APS), 2008)
We measure the mass of the top quark using top-quark pair candidate events in the lepton+jets channel from data corresponding to 1fb-1 of integrated luminosity collected by the D0 experiment at the Fermilab Tevatron collider. We use a likelihood technique that reduces the jet energy scale uncertainty by combining an in situ jet energy calibration with the independent constraint on the jet energy scale (JES) from the calibration derived using photon+jets and dijet samples. We find the mass of the top quark to be 171.5±1.8(stat. +JES)±1.1(syst.)GeV. © 2008 The American Physical Society.